Mandatory Subjects of Constitutional Proceedings in Cases Arising from Citizens’ Appeals to the Constitutional Court of the Russian Federation (VERITAS LEGIS JOURNAL, 2025)
This article is devoted to the study of the subject composition of constitutional proceedings in cases considered by the Constitutional Court of the Russian Federation regarding the constitutionality of laws based on citizens’ appeals. The legal status of mandatory subjects — the Constitutional Court of the Russian Federation and the parties involved in the process — is analyzed, as well as their roles at various stages of judicial proceedings. Special attention is given to the specificity of constitutional proceedings as a distinct type of justice aimed at ensuring the supremacy of the Constitution, protecting citizens’ rights and freedoms, and verifying the constitutionality of normative legal acts. The article examines the legal foundations and procedural powers of the subjects, their participation in evidence collection and decision-making, as well as comparative aspects with foreign systems of constitutional control. The study emphasizes the importance of adhering to constitutional principles and norms, as well as the unique role of the Constitutional Court of the Russian Federation as the highest body of constitutional oversight.Within the context of the conducted analysis, the criteria for classifying participants as mandatory subjects are identified and their significance for ensuring the procedural guarantees of the applicant is substantiated. Particular attention is paid to the impact of the composition of mandatory participants on the admissibility of a constitutional complaint, the scope of case consideration, and the quality of the final law-enforcement outcome. The paper proposes directions for improving the procedural status of the parties in order to enhance the effectiveness of constitutional judicial protection.
Keywords: Constitutional proceedings, Constitutional Court of the Russian Federation, subjects of the constitutional process, mandatory subjects, parties to the process, rights and obligations of participants, constitutional complaint, protection of citizens’ rights, verification of the constitutionality of laws, procedural powers.